Penerapan Metode Wahdah Dalam Meningkatkan Kualitas Hafalan Al-Qur’an Siswa di MA Darul Arqam Sawangan Depok - Mundiatul Mila (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research is motivated by the problem of the low quality of memorization of the Quran in tahfidz subjects in class XI MA Darul Arqam Sawangan Depok. The method in this study uses a class action research method through four steps, namely: planning, action, observation and reflection. In this study, the subjects are students of class XI MA Darul Arqam Sawangan Depok in the 2021/2022 school year consisting of 23 students. The object in this study is to improve the quality of students' Quran memorization using the wahdah method in class XI MA Darul Arqam Sawangan Depok. The improvement in the quality of students' Quran memorization in the learning process also improved. It can be seen from each cycle that it has increased. In the pre-cycle the results obtained were 30%, increasing in cycle I by 43% and in cycle II to 86%. From the learning activities that have been carried out, the percentage of the quality of the students' memorization of the Koran has increased and has reached the predetermined success criteria. This shows that the wahdah method is successful in improving the quality of memorization of the Quran of class XI MA Darul Arqam students in Tahfidz learning. Keywords: Memorization Quality;Quran, Wahdah